(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study aims to evaluate the effect of Clostridium perfringens sialidase treatment on monolayer cell behavior using computational screening and an in vitro approach to demonstrate interaction between enzyme-based drugs and ligands in host cells. Materials and Methods: The in silico study was carried out by molecular docking analysis used to predict the interactions between atoms that occur, followed by genetic characterization of sialidase from a wild isolate. Sialidase, which has undergone further production and purification processes exposed to chicken embryonic fibroblast cell culture, and observations-based structural morphology of cells compared between treated cells and normal cells without treatment. Results: Based on an in silico study, C. perfringens sialidase has an excellent binding affinity with Neu5Acα (2.3) Gal ligand receptor with Gibbs energy value (∆G)—7.35 kcal/mol and Ki value of 4.11 µM. Wild C. perfringens isolates in this study have 99.1%–100% similarity to the plc gene, NanH, and NanI genes, while NanJ shows 93.18% similarity compared to the reference isolate from GenBank. Sialidase at 750 and 150 mU may impact the viability, cell count, and cell behavior structure of fibroblast cells by significantly increasing the empty area and perimeter of chicken embryo fibroblast (CEF) cells, while at 30 mU sialidase shows no significant difference compared with mock control. Conclusion: Sialidase-derived C. perfringens has the capacity to compete with viral molecules for attachment to host sialic acid based on in silico analysis. However, sialidase treatment has an impact on monolayer cell fibroblasts given exposure to high doses. J. Adv. Vet. Anim. Res., 10(4): 667–676, December 2023 http://doi.org/10.5455/javar.2023.j722